DETERMINAN KEJADIAN LUAR BIASA (KLB) RUBELLA DI DESA MUNDEH, SELEMADEG BARAT, TABANAN - DAP Ratna Juwita; Luh Gede Pradnyawatim; Ni Made Hegard Sukmawati (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: Rubella is a contagious person to person viral infection and remains a fetal malformation on pregnancy as congenital rubella syndrome. Under the outbreaks-based rubella surveillance in West-Selemadeg Village, Tabanan Regency in 2019, we investigated the rubella outbreak determinants. Methods: This study investigated 29 suspected cases using major criteria (fever and rash) following with minor criteria criteria (conjunctivitis, malaise, rhinorea, loss appetite and cough) between Juli-September 2019 receiving active and passive surveillans. Altogether, 3 serum samples we received from 5 districts and 29 suspected cases from local health centres. Samples were tested for the measles and rubella IgM antibody. This study measures the determinants of outbreaks using case-control study follows by total population one control design for each sample. Data was analyzed using SPSS with 5% alpha. Results: The attack rate are 58.6% in 5-15yo age and 8.99% based on place (Auman Delod Seme district). The type of epidemiologic curve is propagated epidemic curve (person to person disease) with 11 days means of incubation periode. This outbreaks is associated to person to person close contact (OR 3,4:95%CI 1.009-10.318, p≤0.05 and history of rubella vaccination OR 0.482, 95%CI:0.165-1.409, p≤0.05 with all laboratorium samples positively detected for IgM of rubella viruses. Conclusions: Eradication of rubella is considered to be feasible and beneficial that we need to work toward elimination with a focus on strengthening ongoing immunization.